2019
DOI: 10.3389/fmicb.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Molecular Epidemiology, Transmission Clusters and Transmitted Drug Resistance Mutations in Central Brazil

Abstract: We aimed to characterize HIV-1 molecular epidemiology and transmission clusters among heterosexual (HET) and men who have sex with men (MSM) individuals, as well as transmitted drug resistance mutations (TDRM) in Central-Western Brazil. This cross-sectional survey was conducted among 190 antiretroviral naïve HIV-1 infected individuals. Proviral DNA was extracted, and nested PCR amplified partial polymerase gene (PR/RT). After sequencing, subtypes were assigned, and the sequences were analyzed for the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
(60 reference statements)
5
11
0
Order By: Relevance
“…The lower frequency of NRTI and PI associated mutations observed in this study are in agreement with previously conducted studies among ART-naive individuals in Ethiopia [16,17,23,31,32]. Likewise, similar NRTI and PI associated PDRMs were reported in other countries like Brazil [26] and India [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lower frequency of NRTI and PI associated mutations observed in this study are in agreement with previously conducted studies among ART-naive individuals in Ethiopia [16,17,23,31,32]. Likewise, similar NRTI and PI associated PDRMs were reported in other countries like Brazil [26] and India [25].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a study done in Brazil among ART-naive pregnant women indicated a lower PDR detection rate [ 24 ]. In addition to the above previously published data from Ethiopia, this finding is in agreement with studies done in India [ 25 ], Brazil [ 26 28 ], China [ 29 ], and Iran [ 30 ], which reported a moderate magnitude of PDR among HIV-1 antiretroviral adults. The absence of PDRM screening before starting ART and poor level of adherence might have contributed to this increment of PDR in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, only the M46L PI resistance mutation was detected, which is associated with reduced susceptibility to atazanavir (ATV) and lopinavir (LPV). The low prevalence of PI mutations found (1.3%) is in accordance with other national studies (Arruda et al, 2018;Crispim et al, 2019;Tanaka et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…As reported elsewhere (Arruda et al, 2018), NNRTI mutations predominated in our study and the 14.7% prevalence rate here found was higher than those reported in a Brazilian nationwide study (5.8%; ranging from 4.5% in Central-West and Northeast to 7.0% in South) (Arruda et al, 2018). The most frequent NNRTI mutation detected, K103N (6.7%) was also observed in high rates in other studies conducted in Brazil (Bermúdez-Aza et al, 2011;Arruda et al, 2018;Crispim et al, 2019;Tanaka et al, 2019). It is a non-polymorphic mutation that causes high-level resistance to nevirapine (NVP) and efavirenz (EFV).…”
Section: Discussionsupporting
confidence: 48%
“…Although the B subtype is dominant in South America, F1 and C clades cocirculates at high levels, generating a growing number of circulating recombinant forms (CRFs) and unique recombinant forms (URFs), making the epidemic of this continent highly complex 9 10. In Italy, among non-B subtypes, F1, A1 and C clades are prevalent, affecting 77.2% of HEs 11.…”
Section: Introductionmentioning
confidence: 99%